2007
DOI: 10.1111/j.1526-4610.2007.00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Metabolism is Altered in Migraineurs: A New Pathogenic Mechanism for Migraine?

Abstract: Blood glucose levels may be high in headache patients, but do not seem to be specific to migraineurs. Insulin levels were higher in migraineurs, and seemed specific to this group. These findings are in keeping with recent reports on the effects of insulin on brain functions and lend support to the possibility that insulin is involved in the pathogenesis of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 29 publications
8
69
1
Order By: Relevance
“…Lastly, I/C ratio was significantly different between the three groups with I/C ratio on average lower in male migraineurs and higher in female migraineurs. Recent work comparing glucose and insulin concentrations in migraineurs, headache patients, and non-migraine/headache controls has confirmed that while an elevation in glucose may be associated with headaches in general, an elevated insulin level is specific to migraineurs [7]. In the present study we noted a non-significant trend for a higher plasma glucose level following a sucrose load in migraineurs with the level of plasma glucose becoming significantly elevated in migraineurs at 150-min.…”
Section: Discussionsupporting
confidence: 71%
“…Lastly, I/C ratio was significantly different between the three groups with I/C ratio on average lower in male migraineurs and higher in female migraineurs. Recent work comparing glucose and insulin concentrations in migraineurs, headache patients, and non-migraine/headache controls has confirmed that while an elevation in glucose may be associated with headaches in general, an elevated insulin level is specific to migraineurs [7]. In the present study we noted a non-significant trend for a higher plasma glucose level following a sucrose load in migraineurs with the level of plasma glucose becoming significantly elevated in migraineurs at 150-min.…”
Section: Discussionsupporting
confidence: 71%
“…Cavestro [32] compared glucose and insulin concentrations in 84 migraineurs, 25 headache patients, and 26 nonmigraine/headache controls and confirmed that an elevation in glucose may be associated with headaches in general, but elevated insulin level seems to be specifically associated with migraine attacks.…”
Section: Fasting Glucose Metabolism and Migrainementioning
confidence: 99%
“…Current studies by Rainero et al (1) and Cavestro et al (2) show that insulin sensitivity is impaired in migraine patients, which suggests a role for insulin resistance in the comorbidity of migraine and vascular diseases. Impaired insulin sensitivity in migraine patients is of particular interest, as insulin resistance has emerged as a risk factor for coronary artery disease, hypertension and stroke (3)(4)(5).…”
Section: Introductionmentioning
confidence: 97%